Effects of a 4-Week Very Low-Carbohydrate Diet on High-Intensity Interval Training Responses - Cipryan, Lukas; Plews, Daniel J; Ferretti, Alessandro; Maffetone, Phil B; Laursen, Paul B (Journal of sports science & medicine, 2018)
The purpose of the study was to examine the effects of altering from habitual mixed Western-based (HD) to a very low-carbohydrate high-fat (VLCHF) diet over a 4-week timecourse on performance and physiological responses during high-intensity interval training (HIIT). Eighteen moderately trained males (age 23.8 ± 2.1 years) consuming their HD (48 ± 13% carbohydrate, 17 ± 3% protein, 35 ± 9% fat) were assigned to 2 groups. One group was asked to remain on their HD, while the other was asked to switch to a non-standardized VLCHF diet (8 ± 3% carbohydrate, 29 ± 15% protein, 63 ± 13% fat) for 4 weeks. Participants performed graded exercise tests (GXT) before and after the experiment, and an HIIT session (5x3min, work/rest 2:1, passive recovery, total time 34min) before, and after 2 and 4 weeks. Heart rate (HR), oxygen uptake (V̇O2), respiratory exchange ratio (RER), maximal fat oxidation rates (Fatmax) and blood lactate were measured. Total time to exhaustion (TTE) and maximal V̇O2 (V̇O2max) in the GXT increased in both groups, but between-group changes were trivial (ES ± 90% CI: -0.1 ± 0.3) and small (0.57 ± 0.5), respectively. Between-group difference in Fatmax change (VLCHF: 0.8 ± 0.3 to 1.1 ± 0.2 g/min; HD: 0.7 ± 0.2 to 0.8 ± 0.2 g/min) was large (1.2±0.9), revealing greater increases in the VLCHF versus HD group. Between-group comparisons of mean changes in V̇O2 and HR during the HIIT sessions were trivial to small, whereas mean RER decreased more in the VLCHF group (-1.5 ± 0.1). Lactate changes between groups were unclear. Adoption of a VLCHF diet over 4 weeks increased Fatmax and did not adversely affect TTE during the GXT or cardiorespiratory responses to HIIT compared with the HD.
Keywords: High-Intensity Interval Training; fyzická vytrvalost; Exercise Test; kyselina mléčná; spotřeba kyslíku; Oxygen Consumption; High-intensity exercise; Lactic Acid; mužské pohlaví; ketosis; Sports Nutritional Physiological Phenomena; dieta s omezením sacharidů; Adult; mladý dospělý; Diet, Carbohydrate-Restricted; Heart Rate; vysoce intenzivní intervalový trénink; srdeční frekvence; Young Adult; Lipid Metabolism; Humans; Physical Endurance; graded exercise test; metabolismus lipidů; fyziologie sportovní výživy; zátěžový test; sportovní výkon; Athletic Performance; low-carbohydrate diet; dospělí; high-fat diet; lidé; Male